Political System In The Republic Of Macedonia And EU - NATO Membership Challenges - Zejneli, Jusuf; Maksuti, Bekim (European Scientific Journal, ESJ, 2016)
The basic functioning of institutions in a country depends on the forms of governance. This is defined on the Constitution of the respective state as the highest legal act. It also depends on the practice functioning of the fundamental institutions in a political system. Macedonia has set parliamentary democracy as a form of governance. However, the functioning of the legal system displays different features, because we are dealing with a multiethnic State, the status of candidate country for membership in EU, and NATO – at the same time, faced with the terms of meeting the criteria for euro – Atlantic membership. Although Macedonia is determined to have representative democracy as a form of governance, institutions are functioning with very special specifications. They constantly create new practices, such as frequent elections and early parliamentary Self-dissolution of parliament which was aimed at overcoming the political crisis. There was also an annulment of the decision of the assembly and practices of the practical operation of institutions. However, this makes parliamentary life in Macedonia to be specific from other democratic standards. Specific issue involving the constitutional and legal position of the communities, at various times, has been regulated in different forms. Furthermore, it is more advanced after the signing of the Ohrid Framework Agreement in 2001. At the same time, it presents a challenge in itself and provides an act of harmonized internal legislation to the European Union. This is with genuine parliamentarian debates because the harmonization of legislation requires the implementation of the same laws. Also, it does not just adopt them without been harmonized with the reality in the country.